Psychosocial factors associated with early booking and frequency of antenatal care (ANC) visits in a rural and urban setting in south Africa - Muhwava, Lorrein Shamiso (Department of Public Health and Family Medicine, 2015)
Late antenatal care (ANC) booking remains the trend in most countries in sub- Saharan Africa despite the known benefits of early booking. Infrequent, poor and no antenatal care are among the most frequent patient-related avoidable factors and missed opportunities identified for many cases of maternal death in South Africa. Whilst most country guidelines recommend that a woman initiates antenatal care (ANC) within the first 16 weeks of pregnancy and the Basic Antenatal Care (BANC) approach recommends at least 4 visits during pregnancy, this has not translated into practice amongst women in South Africa. Disparities in timing of initiation of antenatal care and frequency of attendance exist between countries and between rural and urban settings within a country. Previous studies have identified demographic factors, physical access to health facilities, parity, lack of health education, relationships with health care providers and misconceptions of antenatal care (ANC) as factors influencing timing of ANC booking. Psychosocial factors have been found to also play an important role in timing and frequency of attendance to antenatal care. Strong social capital and social support were identified as protective factors against late ANC initiation and inadequate attendance whilst substance use, experiencing negative feelings about the pregnancy, misconceptions about antenatal care, poor mental health were mostly associated with poor ANC attendance. In the literature, partner characteristics and cultural and religious beliefs were associated with both early and late ANC initiation depending on the specific factors investigated. Research on the associations between psychosocial factors and antenatal care attendance is currently quite limited and fairly new and in addition, some psychosocial factors may not be associated with timing of initiation but may have an effect on the frequency of attendance of follow-up visits. The aim of the study was to examine the association between psychosocial factors and ANC booking to determine whether psychosocial factors (particularly substance use, feelings about pregnancy, social capital, social support, cultural beliefs, mental health perceptions, self-esteem and partner characteristics) were associated with not only timing of initiation of antenatal care but also frequency of attendance of antenatal care visits during a previous pregnancy among women in an urban and rural location in South Africa.